2017
DOI: 10.1177/1098612x17734066
|View full text |Cite
|
Sign up to set email alerts
|

Serum symmetric dimethylarginine and creatinine in Birman cats compared with cats of other breeds

Abstract: Objectives The aim of this study was to assess whether, in contrast to serum creatinine, which is higher in Birman cats than in other breeds, the serum concentration of symmetric dimethylarginine (SDMA) is comparable in clinically healthy Birmans and in the general feline population. This could allow, in this breed, to better evaluate chronic kidney disease (CKD). Methods Serum creatinine and SDMA were measured in clinically healthy Birmans (n = 50) and in cats of other breeds (n = 46), and the results were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…One study has suggested that SDMA may be a more accurate reflection of renal function in Birman cats than creatinine concentration although direct GFR and renal imaging were not performed (Paltrinieri et al . 2018). A recent study comparing serum SDMA concentrations in clinically healthy greyhounds to that in other breeds, concluded that greyhounds have significantly higher mean serum SDMA concentrations compared to dogs of other breeds (13.1 and 10.2 μg/dL, respectively) (Liffman et al .…”
Section: Non‐renal Influences On Symmetric Dimethylarginine (Specificmentioning
confidence: 99%
“…One study has suggested that SDMA may be a more accurate reflection of renal function in Birman cats than creatinine concentration although direct GFR and renal imaging were not performed (Paltrinieri et al . 2018). A recent study comparing serum SDMA concentrations in clinically healthy greyhounds to that in other breeds, concluded that greyhounds have significantly higher mean serum SDMA concentrations compared to dogs of other breeds (13.1 and 10.2 μg/dL, respectively) (Liffman et al .…”
Section: Non‐renal Influences On Symmetric Dimethylarginine (Specificmentioning
confidence: 99%
“…Symmetric dimethylarginine (SDMA), a new biomarker for the early detection of kidney dysfunction, is routinely used in human and small animal medicine. SDMA is an endogenous methylated form of the arginine that is released into circulation during normal protein catabolism [ 11 ]. Ninety percent of SDMA is excreted by the kidneys into urine in an unchanged form [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…SDMA, a biomarker enabling early detection of impaired kidney function, is routinely used in human and companion animal medicine. It is an endogenous methylated arginine released into the bloodstream during normal protein catabolism [22]. Physiologically, 90% of SDMA is excreted in an unchanged form with urine [19,23,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in horses have attempted to evaluate renal function by analysis of the fractional excretion of sodium (FENa), urine γ-glutamyl transpeptidase to creatinine ratio (GGT:Crea), as well as cystatin C and neutrophil gelatinase-associated lipocalin (NGAL) levels, but with inconsistent results [8,[16][17][18]. Studies in human and companion animals, on the other hand, assessed multiple serum and urinary parameters as potential AKI biomarkers, symmetric dimethylarginine (SDMA) being the most common [19][20][21][22][23][24][25]. SDMA levels have previously been determined in healthy adult horses and in neonatal foals [26][27][28] but only one study has assessed SDMA in horses with kidney dysfunction; however a different diagnostic test was used [29].…”
Section: Introductionmentioning
confidence: 99%